2013
DOI: 10.1080/19425120.2013.824941
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Density‐Dependent Changes in Growth and Maturity of the Barndoor Skate on Georges Bank

Abstract: Drastic increases or decreases in biomass often result in density‐dependent changes in life history characteristics within a fish population. Acknowledging this phenomenon and in light of the recent biomass increase in Barndoor Skate Dipturus laevis, the current study re‐evaluated the growth rate and sexual maturity of 244 specimens collected from 2009–2011within closed areas I and II on Georges Bank, USA. Ages were estimated using vertebral band counts from skate that ranged from 21 to 129 cm TL. The von Bert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The comparisons by Jennings et al (), however, assumed fixed life‐history parameters throughout their time series. Changing life‐history parameters, such as ages at maturity (Coutré et al , ) or sizes at maturity (Paesch & Oddone, ; this study), are seldom reported for skates in relation to abundance changes, but have been noted for other elasmobranchs (Sminkey & Musick, ; Sosebee, ; Cassoff et al , ).…”
Section: Discussionmentioning
confidence: 53%
“…The comparisons by Jennings et al (), however, assumed fixed life‐history parameters throughout their time series. Changing life‐history parameters, such as ages at maturity (Coutré et al , ) or sizes at maturity (Paesch & Oddone, ; this study), are seldom reported for skates in relation to abundance changes, but have been noted for other elasmobranchs (Sminkey & Musick, ; Sosebee, ; Cassoff et al , ).…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, these differences may be related to different regional scales or may be explained by the fact that there are several years of intense exploitation of this species between these two studies. Empirical evidence of density‐dependent changes has been reported for elasmobranchs species that have suffered harvesting over several years, involving changes in their biological parameters (Carlson & Baremore, 2003; Coutré et al, 2013; Sminkey & Musick, 1995; Sosebee, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bathyraja griseocauda (Norman 1937) in Patagonian waters attain 1570 mm TL and a maximum age of 28 years (Arkhipkin et al ., 2008), Beringraja rhina (Jordan and Gilbert 1880) from the Gulf of Alaska attain 1400 mm TL and a maximum age of 25 years (Gburski et al ., 2007) and Dipturus oxyrinchus (L. 1758) from the Gulf of Gabés in the Mediterranean attain 1500 mm TL and a maximum age of 25 years (Kadri et al ., 2014a). Comparing age and growth parameters of the same species on a regional scale may help to monitor populations and identify potential long‐term effects of fishing pressure (Coutré et al ., 2013). For this reason, it is important to have a common criterion for age readings and growth parameter estimations, because the differences will not allow to adequately identify temporal changes in life‐history traits within the same population.…”
Section: Discussionmentioning
confidence: 99%
“…In Argentinian and Uruguayan waters, this species occurs from shallow coastal waters to approximately 100 m depth (Cousseau et al, 2007). A. castelnaui is a predator with a narrow trophic niche breadth, feeding almost exclusively on teleost fishes (Barbini et al, 2020;Barbini & Lucifora, 2012).…”
Section: Introductionmentioning
confidence: 99%